An Analysis of the Influences of Individual Optimism, Risk Taking and Self-Confidence on Professional Accounting Judgment - Victoria Bogdan; Ioana Teodora Meşter; Dana Gherai; Carmen Mihaela Scorțe (Journal of Accounting and Management Information Systems (JAMIS), 2017)
Chaotic dynamics of today's global business environment exert a tremendous pressure on professionals accounting judgment performance. A survey was mailed to Romanian professional accountants to examine their perception on accounting judgments and decisions. The results based on 531 valid responses indicate that professionals considered that a judgment in accounting is influenced by the responsibility of the accountant in preparing the financial statements according to the regulatory financial reporting framework. Also, they think that an adequate accounting judgment is best characterized by: "logical, consistent and substantiated", characteristics. Exploring statistical differences between accountants, grouped by age, gender, as well as years of practice, we found that younger investigated accountants are more optimistic that the ones over 45. We have used Chi-Square test and Pearson's correlation coefficient and showed that there is a correlation between accountants' propensity towards optimism and their perception regarding the need of a theoretical framework of JDM, and between accountants' propensity towards risk and their choice regarding the aspects that influence accounting judgment. Also, accountants' self-confidence is in direct correlation with their opinion regarding the aspects that influence JDM in accounting, but there is no statistical correlation between accountants' propensity towards optimism and their choice regarding the aspects that influence accounting judgment. Our results showed that is on interest to further investigate these correlations to identify new ways to improve JDM in accounting. The role of professional accountant is shaped by the pressure of several external factors that also mark their behavior, hence, accountants are not robots, are humans.
Keywords: M41; A14; Z13; 650; professional accountants; judgment and decision making; optimism; risk taking; self-confidence